Systematic free energy insights into the enhanced dispersibility of myofibrillar protein in low-salt solutions through ultrasound-assisted enzymatic deamidation - Yating Liu; Zongyun Yang; Zhen Li; Juan Shen; Xia Wang; Ru Li; Ye Tao; Xinglian Xu; Peng Wang (Ultrasonics Sonochemistry)
This work aimed to investigate the effects of ultrasound assisted enzymatic deamidation by protein-glutaminase (PG) on the dispersion of myofibrillar protein (MP) in low-salt solutions. The solubility, structural characteristics, transmission electron microscopy, asymmetric-flow field-flow fractionation, steady shear rheological property and multiple light scattering of MP deamidated by PG (MP-PG) and MP pretreated with ultrasound followed by PG deamidation (MP-U-PG) were determined. Molecular docking and molecular dynamics (MD) simulations were used to estimate the interaction between PG and MP. Under ultrasound assistance, the MP deamidated for 16 h (MP-U-PG16) showed the highest solubility (80.1 %) in low-salt conditions, which is attributed to its highest absolute zeta potential and smallest particle size. Although secondary structure analysis showed that MP-PG and MP-U-PG had an increased α-helix ratio and a decreased β-sheet ratio, ultrasonic treatment had a significantly influence on the MD results. The results manifested that hydrogen bond was the primary forces driving the binding between PG and MP, and the hydrogen bond and hydrophobic interaction were the dominant forces responsible the binding between PG and MP pretreated with ultrasound. According to the energy landscapes theory, ultrasound could overcome the energy barriers through external force input and find the best pathway to achieve the final lowest energy state. Our research contributed to the improvement of the colloidal dispersibility of MPs under low-salt conditions and the regulation of protein interaction by ultrasound assistance.